Isolation ratio and T-serotyping of group A streptococci from pediatric upper respiratory tract infections in Turkey - (:unkn) unknown (My University, 2005)
Objective: Acute rheumatic fever can follow throat infections with group A streptococci. Certain serotypes of group A streptococci such as M1, M3, M5, M6, M14, M18, M19, M24 are associated with this disorder. Immunity to streptococci and to rheumatic fever depends on antibodies to the M proteins. Due to current scarcity of M-typing sera, many laboratories use T typing and opacity factor production for serotype identification of group A streptococci. In order to, investigate the most common serotypes of group A streptococci in our country in recent years we studied T-agglutination typing and opacity factor of 120 group A streptococci strains isolated from throat cultures of 930 children. Methods: Diffuse, stable suspensions of group A streptococci were tested with polyvalent antisera (T,U,W,X,Y) by slide agglutination. Microplate method was used for opacity factor detection. Results: T-protein -agglutination patterns U (2,4,6,28) were the most common among typeable strains. The rate of T-protein -agglutination patterns T (1,3,13, B3264) and X (8,14,25,lmp.19) were 20% and 18% respectively. Opacity factor production rate of isolated group A streptococci strains was 65%. Conclusion: To profit global assessment of rheumatic fever and rheumatic heart disease, more epidemiologic and serotyping research is required in our country.
Keywords: Group A streptococcus; Isolation rate; Serotyping